2019
DOI: 10.1002/bit.27182
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Escherichia coli for propionic acid production through the Wood–Werkman cycle

Abstract: Native to propionibacteria, the Wood–Werkman cycle enables propionate production via succinate decarboxylation. Current limitations in engineering propionibacteria strains have redirected attention toward the heterologous production in model organisms. Here, we report the functional expression of the Wood–Werkman cycle in Escherichia coli to enable propionate and 1‐propanol production. The initial proof‐of‐concept attempt showed that the cycle can be used for production. However, production levels were low (0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 50 publications
1
15
0
Order By: Relevance
“…This advantage comes with the limitation to operate in anaerobic conditions considering one of the enzymes within the cycle (mutase) is inhibited by oxygen, therefore limiting the availability of ATP required to support the synthesis of polyketides. However, the Wood-Werkman cycle provides an alternative for the generation of energy by allowing the operation of the electron transport chain by using fumarate as terminal electron acceptor [17]. Here, we tested whether that energetic surplus could make it possible to sustain polyketide production during a single-stage anaerobic process.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This advantage comes with the limitation to operate in anaerobic conditions considering one of the enzymes within the cycle (mutase) is inhibited by oxygen, therefore limiting the availability of ATP required to support the synthesis of polyketides. However, the Wood-Werkman cycle provides an alternative for the generation of energy by allowing the operation of the electron transport chain by using fumarate as terminal electron acceptor [17]. Here, we tested whether that energetic surplus could make it possible to sustain polyketide production during a single-stage anaerobic process.…”
Section: Discussionmentioning
confidence: 99%
“…We evaluated the feasibility of using a synthetic Wood-Werkman cycle as a source of propionyl-CoA and S-methylmalonyl-CoA, the intermediaries required for the synthesis of 6-dEB. Previously, we demonstrated that under anaerobic conditions, E. coli can produce propionate via the Wood-Werkman cycle using a plasmid system which encodes a single operon (10 kb) under the control of the P BAD promoter [17]. We decided to use the same expression system in 6-dEB producer strain, E. coli 207-3.…”
Section: Assembling a Three-plasmid System For The Production Of 6-deb In E Colimentioning
confidence: 99%
See 1 more Smart Citation
“…Their combination with glucose and glycerol as carbon sources results in increased acid concentration and higher productivity ( 70 ). Productivity can also be improved by the application of metabolic engineering, for which Escherichia coli is the most widely used host ( 71 ). Phosphoenolpyruvate carboxylase enzyme from Escherichia coli has been cloned into Propionibacterium freudenreichii .…”
Section: Process Parameters Influencing Microbial Production and Prodmentioning
confidence: 99%
“…Currently, pathway design and optimization are essential to obtain microbial cell factories with excellent performance for industrial production of commercial chemicals ( 15 , 16 ). A series of attempts have been made to construct novel producers for biobased chemicals as the technologies in support of synthesizing new materials and manipulating genes have matured ( 17 19 ). Indeed, some strategies have been applied to optimize the biosynthetic pathways, which consist of large numbers of genes, or to reprogram gene expression to manipulate complex phenotypes.…”
Section: Introductionmentioning
confidence: 99%